Hubungan Self-Regulated Learning dengan Prokrastinasi Akademik pada Mahasiswa Pengguna Game Online di Kota Padang - Pratiwi, Miranda (Lembaga Yasin AlSys, 2024)
The purpose of this study was to see the relationship between self-regulated learning and academic procrastination in students who use online games in Padang City. The data collection technique used in this study was a questionnaire. The population in this study were students who use online games in Padang City. The sample in this study amounted to 100 respondents. Based on the results of testing the variables of self-regulated learning and academic procrastination, it has been done using Pearson product moment correlation analysis, showing that the magnitude of the relationship between self-regulated learning and academic procrastination is p value = 0.000 (<0.05). That means Ha there is a relationship between self-regulated learning and academic procrastination in students who use online games in Padang City is proven because the value is p> 0.05.